Concentrations of trace metals in selected land uses of a dry zone soil catena of Sri Lanka - F. Rosemary; U.W.A. Vitharana; S.P. Indraratne; S.V.R. Weerasooriya (Tropical Agricultural Research, 2015)
Assessment of environmental risk associated with the pollution of trace metals is important for proper management of soils. This study was conducted to find out the present level of trace metals, their sources and the relationships among them in selected land uses. A Dry Zone soil catena consisting of uncultivated, paddy-cultivated and vegetablecultivated land uses was selected for this study. A total of 58 soil samples were collected on the basis of latin hypercube sampling approach. Soil samples were analyzed for the total concentrations of Cd, Cu, Pb, Ni and Zn. Exploratory data analysis, correlation analysis, mean comparison test and principal component analysis (PCA) were performed for the data. All the trace metals analyzed were below the maximum permissible levels in the soil catena studied. An accumulation of Cd was observed in paddy lands. The PCA confirmed the contribution of anthropogenic factors on Cd levels observed in this Dry Zone soil catena. Copper and Ni concentrations did not vary among the selected land uses while Zn, Cd and Pb concentrations varied with land uses. A strong and a significant relationship between Cu and Zn in all three land uses indicated a common origin of these metals. The PCA indicated that Cu, Zn and Pb would have originated from the mixed factor of natural and anthropogenic sources. The PCA also indicated the natural origin of Ni in the tested soils. Tropical Agricultural Research Vol. 25 (4): 512-522 (2014)